The Universality of the Universal Declaration of Human Rights: Does it merely express Western Values? - Anam, Syaiful (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2018)
The debate over the universality of Universal Declaration of Human Rights remains taking place. Apart from the fact that the document remains popular and has been encouraged by many countries around the world. The debate revolves around values and cultural differences among countries claiming that Western values have been predominating the content of the declaration itself. This essay argues that the dispute towards the universality of UDHR would likely form a robust standard and values of internationally recognized human rights as long as a cross-cultural and cross-philosophical talk could be encouraged.